Comparison of embolic effect between water‐in‐oil emulsion and microspheres in transarterial embolization for rat hepatocellular carcinoma model. Issue 11 (7th September 2020) - Minamiguchi, Kiyoyuki; Tanaka, Toshihiro; Nishiofuku, Hideyuki; Fukuoka, Yasushi; Taiji, Ryosuke; Matsumoto, Takeshi; Saito, Natsuhiko; Taguchi, Hidehiko; Marugami, Nagaaki; Hirai, Toshiko; Kichikawa, Kimihiko
Abstract : Aim: To compare two different embolic materials, water‐in‐oil (W/O) emulsion followed by gelatin particles and microspheres in transarterial embolization (TAE), using a rat hepatocellular carcinoma model. Methods: Twenty rats bearing N1S1 cells were divided into the W/O emulsion group and Microsphere group. Water‐in‐oil emulsion was created by a glass membrane emulsification device. The tumor vascularity was measured by contrast‐enhanced ultrasonography 24 h before and 10 min and 48 h after TAE. Tumor necrosis, hepatic infarction ratio surrounding the tumor, and locations of the embolic materials 48 h after TAE were assessed. The changes of serum liver enzymes were also evaluated. Statistical significance was determined by using either the Mann–Whitney U ‐test or Fisher's exact test. Results: The tumor vascularity 48 h after TAE was significantly higher in the Microsphere group (20.1 vs. 3.76%, P  = 0.016). The overflow of Lipiodol into the portal veins surrounding the tumor was seen, whereas microspheres were seen only in the artery. The percentage of necrotic area and complete response ratio in the W/O emulsion group was significantly higher (99.9 vs. 87.6%, P  = 0.029 and 87.5 vs. 28.6%, P  = 0.041, respectively). Serum aspartate aminotransferase and serum alanine aminotransferase levels 48 h after TAE were significantly higher in the W/O emulsion group ( P  < 0.01). Conclusions: The embolization using W/O emulsion followed by gelatin particles showed stronger antitumor effects with the occlusion of both the tumor feeding artery and the portal vein compared with microspheres, which occluded only the arteries.